The vulnerability experienced by the family of children hospitalized in a pediatric intensive care unit - Côa, Thatiana Fernanda; Pettengill, Myriam Aparecida Mandetta (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to understand the vulnerability experienced by the family of children hospitalized in a Pediatric Intensive Care Unit (PICU). The Symbolic Interactionism and the Concept of Family Vulnerability were the frameworks used to understand this experience. Qualitative Content Analysis was used. Data was collected through interviews and observation with 11 families of children hospitalized in a PICU of a university hospital in São Paulo. Six analytical categories regarding the family experience emerged. The categories were compared to the conceptual categories of Family and Vulnerability, and revealed the elements that defined the concept within this context. The child's hospitalization in a PICU triggers intense suffering within the family, as it refers to the possibility of losing their child. Thus, the power and the autonomy of the family in relation to their child are reduced, intensifying the feeling of vulnerability.